2009
DOI: 10.1055/s-0029-1212139
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone and vitamin E block stress-induced reduction of locomotor activity and elevation of plasma corticosterone

Abstract: Normal rats, on being repetitively stressed by being restrained in a tight container for two hours, had higher levels of plasma corticosterone compared to pre stress values. These rats also reacted to the stress by a behavioral response in which there was marked decrease in locomotor activity assessed by the open field test (pre stress: 71.3 +/- 2.6 squares crossed versus post stress: 14.3 +/- 2.5 squares crossed) by counting the number of squares entered by the rat over 5 minutes. By the 6th to 7th exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…We have observed a normalization of corticosterone levels by 100 mg/kg a-tocopherol treatment. In agreement with our results, it has been published that plasma corticosterone was significantly reduced to the control values in stressed rats by 150 mg/kg a-tocopherol treatment (Ainsah et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…We have observed a normalization of corticosterone levels by 100 mg/kg a-tocopherol treatment. In agreement with our results, it has been published that plasma corticosterone was significantly reduced to the control values in stressed rats by 150 mg/kg a-tocopherol treatment (Ainsah et al, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…Vitamin E deficiency significantly increased corticosterone concentrations under the stress of the EPM test, and tended to increase under basal conditions (two-way ANOVA, p=0.087 for the effect of diet). It has been reported that corticosterone levels under restraint stress were elevated by vitamin-E deficiency and were reduced by treatment with vitamin E. 25,26) In addition, the association between anxiety and HPA axis reactivity suggests the importance of the HPA axis in anxiety behavior on the EPM test. 13,14) The result that vitamin-E deficiency did not increase anxiety behavior in adrenalectomized rats indicates that corticosterone is important for the anxiogenic effect of vitamin-E deficiency (Terada et al, manuscript in preparation).…”
Section: Con -Ementioning
confidence: 99%
“…Rats have been widely used in stress studies. There is an established model for producing gastric lesions by various methods of stress, such as restraint [1, 2], water-immersion restraint [3] and cold-restraint stress [4]. …”
Section: Introductionmentioning
confidence: 99%
“…It includes factors which disrupt gastric mucosal integrity, such as changes in gastric acid, mucus and bicarbonate secretions, inhibition of gastric mucosal prostaglandin synthesis, reduction of gastric mucosal blood flow [5, 6] as well as changes in stress hormones [1, 3, 7, 8] and gastric motility [9, 10]. …”
Section: Introductionmentioning
confidence: 99%